Fermentation quality and nutritive value of rice crop residue based silage ensiled with addition of epiphytic lactic acid bacteria - Santoso, B; Hariadi, B.Tj.; ., Alimuddin; Seseray, D.Y. (Indonesian Journal of Animal and Veterinary Sciences, 2011)
Silage is the feedstuff resulted from the preservation of forages through lactic acid fermentation. The aim of this study was to evaluate nutritive value, fermentation characteristics and nutrients digestibility of rice crop residue based silage ensiled with epiphytic lactic acid bacteria (LAB). The mixture of rice crop residue (RC), soybean curd residue (SC) and cassava waste (CW) in a 90: 5: 5 (on dry matter basis) ratio was used as silage material. Three treatments silage were (A) RC + SC + CW as a control; (B) RC + SC + CW + LAB inoculums from rice crop residue; (C) RC + SC + CW + LAB inoculums from king grass. Silage materials were packed into plastic silo (1.5 kg capacity) and stored for 30 days. The results showed that crude protein content in B and C silage was higher than that of silage A, but NDF content in silages B and C was lower than that of silage A. Lactic acid concentration was higher (P < 0.01) in silage C compared to silage B and A, thus pH value of silage C was lower (P < 0.01) than silage B and A. Silage C had the highest Fleigh point than that of other silages. Dry matter and organic matter digestibilities were higher in silages B and C (P < 0.01) than that of control silage. It was concluded that the addition of LAB inoculums from king grass to rice crop residue based silage resulted a better fermentation quality compared to LAB inoculums from rice crop residue. Key Words: Silage, Rice Crop Residue, Lactic Acid, In Vitro